[11C]MADAM Used as a Model for Understanding the Radiometabolism of Diphenyl Sulfide Radioligands for Positron Emission Tomography (PET) - Gourand, Fabienne; Amini, Nahid; Jia, Zhisheng; Stone-Elander, Sharon; Guilloteau, Denis; Barré, Louisa; Halldin, Christer (PLOS ONE, 2015)
In quantitative PET measurements, the analysis of radiometabolites in plasma is essential for determining the exact arterial input function. Diphenyl sulfide compounds are promising PET and SPECT radioligands for in vivo quantification of the serotonin transporter (SERT) and it is therefore important to investigate their radiometabolism. We have chosen to explore the radiometabolic profile of [11C]MADAM, one of these radioligands widely used for in vivo PET-SERT studies. The metabolism of [11C]MADAM/MADAM was investigated using rat and human liver microsomes (RLM and HLM) in combination with radio-HPLC or UHPLC/Q-ToF-MS for their identification. The effect of carrier on the radiometabolic rate of the radioligand [11C]MADAM in vitro and in vivo was examined by radio-HPLC. RLM and HLM incubations were carried out at two different carrier concentrations of 1 and 10 μM. Urine samples after perfusion of [11C]MADAM/MADAM in rats were also analysed by radio-HPLC. Analysis by UHPLC/Q-ToF-MS identified the metabolites produced in vitro to be results of N-demethylation, S-oxidation and benzylic hydroxylation. The presence of carrier greatly affected the radiometabolism rate of [11C]MADAM in both RLM/HLM experiments and in vivo rat studies. The good concordance between the results predicted by RLM and HLM experiments and the in vivo data obtained in rat studies indicate that the kinetics of the radiometabolism of the radioligand [11C]MADAM is dose-dependent. This issue needs to be addressed when the diarylsulfide class of compounds are used in PET quantifications of SERT.